2009
DOI: 10.1371/journal.pone.0006594
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Receptor, Lrp5, Is Expressed by Mouse Mammary Stem Cells and Is Required to Maintain the Basal Lineage

Abstract: BackgroundEctopic Wnt signaling induces increased stem/progenitor cell activity in the mouse mammary gland, followed by tumor development. The Wnt signaling receptors, Lrp5/6, are uniquely required for canonical Wnt activity. Previous data has shown that the absence of Lrp5 confers resistance to Wnt1-induced tumor development.Methodology/Principal FindingsHere, we show that all basal mammary cells express Lrp5, and co-express Lrp6 in a similar fashion. Though Wnt dependent transcription of key target genes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 75 publications
10
145
0
Order By: Relevance
“…Notably, when the MaSC marker CD29 is deleted from the basal compartment of the mammary gland, the mammary epithelial cells can no longer reconstitute a new mammary gland, but they can form alveoli late in pregnancy [18], suggesting a distinct MaSC population. Similar results were also obtained when the Wnt receptor LPR5 was deleted [23]. A recent study showed that using a GFP reporter driven by the s-SHIP promoter, GFP + replicating "active" MaSCs can be identified in cap cells in puberty and basal alveolar bud cells in pregnancy, but not in adult virgin animals, or in mammary tissues during lactation or involution stages [16].…”
Section: Identification Of Mascssupporting
confidence: 67%
See 2 more Smart Citations
“…Notably, when the MaSC marker CD29 is deleted from the basal compartment of the mammary gland, the mammary epithelial cells can no longer reconstitute a new mammary gland, but they can form alveoli late in pregnancy [18], suggesting a distinct MaSC population. Similar results were also obtained when the Wnt receptor LPR5 was deleted [23]. A recent study showed that using a GFP reporter driven by the s-SHIP promoter, GFP + replicating "active" MaSCs can be identified in cap cells in puberty and basal alveolar bud cells in pregnancy, but not in adult virgin animals, or in mammary tissues during lactation or involution stages [16].…”
Section: Identification Of Mascssupporting
confidence: 67%
“…For instance, in the Wnt pathway the receptor LRP5 can enrich for MaSCs on its own (although to a lesser degree than CD24 and CD29/ CD49f) and is functionally required for maintaining stem cell populations [23]. Overexpression of Wnt1 using the mammary-specific MMTV promoter resulted in a 6.4-fold increase in the number of MaSCs [7].…”
Section: Signaling Pathways Important For Maintaining Mascsmentioning
confidence: 99%
See 1 more Smart Citation
“…LRP5/6 are presently thought to be required for mammary outgrowths and often overexpressed in breast tumours [4][5][6][7] . Higher expressions of LRP5/6 were also observed in metastatic 4T1 cells than nonmetastatic 168FARN cells (Supplementary Fig.…”
Section: Lrp6 Interacts With Frz Independently Of Wnt Ligandsmentioning
confidence: 99%
“…The canonical Wnt1 gene was originally identified as a preferential integration site for the mouse mammary tumour virus in virally induced breast tumours 3 . Thereafter, LRP5/6 have been identified to be key for Wnt1-dependent tumour development in the Wnt1 transgenic mouse model [4][5][6] and LRP6 is often overexpressed in human breast tumours 7 . Thus, the components of the canonical pathway including LRP5/6 are commonly thought to be involved in cancer development as oncogenes.…”
mentioning
confidence: 99%